2015
DOI: 10.18805/ijar.7034
|View full text |Cite
|
Sign up to set email alerts
|

Status, management practices and performance in three strains of deoni breed of cattle

Abstract: Deoni is an important medium heavy dual purpose cattle breed found mainly in Latur district and also distributed in small numbers in the neighboring districts <italic>viz</italic>. Parbhani, Nanded and Osmanabad of Maharashtra. Deoni cattle have three strains on the basis of coat colour variation <italic>viz</italic>. <italic>Wannera</italic> (clear white with black colour at the sides of the face), <italic>Shevera</italic> (white body with irregular black spots)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 2 publications
3
4
1
Order By: Relevance
“…The overall fat and SNF per cent in milk of Dagri cattle were 4.08±0.40% and 9.18±0.22%. The present finding of fat % was comparable to the findings of Singh et al (2007) in Gangatiri cattle (4.33%); Kuralkar et al (2015) in Deoni cattle (4.20±0.15%); Iype et al (2016) in Kasargod cattle (3.9±0.3%). However, higher values than the present finding were reported by Kayastha et al (2006) in Assam native cattle (5.34±0.06%) and by in Manipur indigenous cattle (5.42±0.03%).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The overall fat and SNF per cent in milk of Dagri cattle were 4.08±0.40% and 9.18±0.22%. The present finding of fat % was comparable to the findings of Singh et al (2007) in Gangatiri cattle (4.33%); Kuralkar et al (2015) in Deoni cattle (4.20±0.15%); Iype et al (2016) in Kasargod cattle (3.9±0.3%). However, higher values than the present finding were reported by Kayastha et al (2006) in Assam native cattle (5.34±0.06%) and by in Manipur indigenous cattle (5.42±0.03%).…”
Section: Resultssupporting
confidence: 91%
“…However, higher values than the present finding were reported by Kayastha et al (2006) in Assam native cattle (5.34±0.06%) and by in Manipur indigenous cattle (5.42±0.03%). While, the overall SNF per cent in milk was higher than that reported by Kayastha et al (2006) in Assam native cattle (8.54±0.03%), by in Manipur indigenous cattle (8.47±0.02%), by Kuralkar et al (2015) in Deoni (8.43±0.05%) and by Iype et al (2016) in Kasargod (8.56±0.17%). It is pertinent to mention that our result is based only on 36 milk samples.…”
Section: Resultsmentioning
confidence: 57%
“…Also, multiparous cows reach their peak in early lactation than first parity cows by consuming more feed and water, leading to longer persistency period than that of the first calving. Our observations corroborate with the reports of Wondifraw et al (2013), Anarase et al (2015), and Kuralkar et al (2015), who reported the highest LMY in fifth and second parity, respectively. The season of calving and period of calving did not have any significant effect on LMY.…”
Section: Lactation Milk Yieldsupporting
confidence: 93%
“…significant effect of season of calving on LL. In contrast, and Kuralkar et al (2015) did not find it's a significant effect on LL.…”
Section: Factors Affecting Lactation Performance Of Deoni Cattlementioning
confidence: 58%
“…Livestock is an integral component of Indian agriculture supporting livelihood of more than two-thirds of the rural population with rich livestock biodiversity with total number of indigenous breeds of cattle (50), buffalo (17), goat (34), sheep (44), horses & ponies (7), camel (9), pig (10), donkey (3), chicken (19) and duck (2) as per recent data released by National Bureau of Animal Genetic Resources, Karnal, India.…”
Section: Introductionmentioning
confidence: 99%